Does cannabis use in adolescence predict self-harm or suicide? : Results from a Finnish Birth Cohort Study - Denissoff, Alexander; Niemelä, Solja; Scott, James G.; Salom, Caroline L.; Hielscher, Emily; Miettunen, Jouko; Alakokkare, Anni Emilia; Mustonen, Antti (Acta Psychiatrica Scandinavica, 2022)
Objective: Longitudinal studies examining the association between adolescent cannabis use and self-harm are rare, heterogeneous and mixed in their conclusions. We study this association utilizing a large general population-based sample with prospective data. Methods: The Northern Finland Birth Cohort 1986 (n = 6582) with linkage to nationwide register data was used to study the association of self-reported cannabis use at age 15–16 years and self-harm and suicide death until age 33 (until year 2018), based on register information. Cox regression analysis with Hazard Ratios (HR) and 95% confidence intervals (CI) was used. Psychiatric disorders, parental psychiatric disorders and other substance use were considered as confounders. Results: In all, 6582 (49.2% male) were included in the analysis, and 377 adolescents (5.7%) reported any cannabis use until the age of 15–16 years. Based on register information, 79 (55.7% male) had visited in health care services due to self-harm, and 22 (90.1% male) had died by suicide. In crude analyses, adolescent cannabis use was associated with self-harm (HR = 3.93; 95% CI 2.24–6.90). The association between cannabis use and self-harm remained statistically significant after adjusting for sex, psychiatric disorders at baseline, frequent alcohol intoxications, other illicit drug use, and parental psychiatric disorders (HR 2.06; 95% CI 1.07–3.95). In contrast, the association of cannabis use with suicide did not reach statistical significance even in crude analysis (HR 2.60; 95% CI 0.77–8.78). Conclusion: Cannabis use in adolescence may increase risk of self-harm independent of adolescent psychopathology and other substance use. Peer reviewed